Evaluation of the Effects of Radiation Therapy on Muscle Contractibility and Skin Healing: An Experimental Study of the Cancer Treatment Implications - Avelino, Sarah O. M. [UNESP]; Neves, Rafael M. [UNESP]; Sobral-Silva, Leonardo A. [UNESP]; Tango, Rubens N. [UNESP]; Federico, Claudio A.; Vegian, Mariana R. C. [UNESP]; de Almeida-Silva, Luis Augusto [UNESP]; Kaminagakura, Estela [UNESP]; Amorim, José Benedito O. [UNESP]; Vasconcellos, Luana M. R. [UNESP] (MDPI, 2023)
Background: Radiotherapy can affect healthy cells, resulting in side effects. This study aimed to assess the impact of radiotherapy on soft tissue in surgical wounds in rats. Methods: The animals were divided into four groups: control (S) group without irradiation, immediate irradiation (S-IIr) group receiving irradiation right after surgery, late irradiation (S-LIr) group receiving irradiation four weeks after surgery, and early irradiation (Ir-S) group receiving irradiation before surgery. The irradiated groups underwent two fractional stages of 15 Gy. Muscle contractibility (EMG) was evaluated at two different time points, and after 2 and 7 weeks, the animals were euthanized for histological analysis of the muscles and skin. Results: There was no significant difference between the EMG1 and EMG2 values of the S and S-LIr groups, but both S-IIr and Ir-S groups exhibited a statistically significant difference. The S group demonstrated a larger diameter of muscle fiber compared to other groups, showing a significant difference. In terms of skin analysis, the S-IIr group had the least inflammatory infiltrate and the highest amount of red fibers, differing significantly from the other groups. Conclusions: Regardless of the duration, radiotherapy was found to have effects on the surrounding soft tissues, as concluded by this study.
Keywords: electromyography; in vivo; muscle; radiotherapy; skin